Research Project Impact Database - Template - De Moura Rocha Lima, Giovanna (Trinity College Dublin, 2022)
This Research Project Impact Database – Template supports research teams in monitoring, accessing and communicating their impact. It is the result of a pilot programme jointly financed by the Office of the Dean of Research and the Trinity Long Room Hub. Please see the Researcher Impact Framework for more: https://doi.org/10.25546/98474.
This Research Project Impact Database – Template is developed to support research teams in monitoring, accessing and communicating their impact. It is the result of a pilot programme jointly financed by the Office of the Dean of Research and the Trinity Long Room Hub. This template is for general guidance and informational purposes only. It is not intended to be authoritative in what research teams may decide to monitor, access and communicate. Edits are strongly encouraged to make this template fit the team’s journey and particularly any funding requirements they may need to report on. It contains links to other third-party websites for convenience of the user but should not be understood as an endorsement of these sites. The author is grateful to the teams at the Office of the Dean of Research, the Trinity Long Room Hub, the Research Informatics Unit and the entire Trinity College Dublin community for the multiple engagement and knowledge exchange opportunities that fed into this work, particularly the teams responsible for the SHAPE-ID and IDS-TILDA projects.
Keywords: research impact; database; DATABASE; Evidence based practice; Evidence-Based Practice; IMPACT; research impact; societal impact